The Influence of Applying the Qiro’ati One Day One Page Method on the Quality of Al-Qur’an Reading for Class VII Students at MTS Nahdatul Islam Mancang - Ibrahim Hasan; Khasanuddin . (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
The problem in this research is that there are problems at MT's Nahdatul Islam school, namely the lack of students reading the Al-Qur'an using tajwid knowledge and the low level of students reading the Al-Qur'an. By applying the Qiro'ati One Day One Page method, the aim is to find out how this method influences the quality of Al-Qur'an reading in class VII MT's Nahdatul Islam Mancang. There is a type of research, namely quantitative experiment, which is a quantitative research method used to determine the effect of independent variables (treatment) on dependent variables (outcomes) under controlled conditions. From the coefficient results it can be concluded that the correlation value of "r" product moment at the 5% and 1% significance levels shows that r = 0.483 is greater than rabe at both the 5% and 1% significance levels (0.5052 and 0.6178) with a comparative formulation, namely (0.4830.5052 and 0.6178).